2021
DOI: 10.3389/fgeed.2020.623717
|View full text |Cite
|
Sign up to set email alerts
|

Non-immunogenic Induced Pluripotent Stem Cells, a Promising Way Forward for Allogenic Transplantations for Neurological Disorders

Abstract: Neurological disorder is a general term used for diseases affecting the function of the brain and nervous system. Those include a broad range of diseases from developmental disorders (e.g., Autism) over injury related disorders (e.g., stroke and brain tumors) to age related neurodegeneration (e.g., Alzheimer's disease), affecting up to 1 billion people worldwide. For most of those disorders, no curative treatment exists leaving symptomatic treatment as the primary mean of alleviation. Human induced pluripotent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 149 publications
(166 reference statements)
0
11
0
1
Order By: Relevance
“…The results of these studies will probably help clarifying which is the most optimal source for the development of large-scale therapies in humans. The banking of fully characterized HLA-matched/ablated ESC and iPSC lines produced under cGMP conditions will allow the use of the same lines in both preclinical and clinical studies, favoring standardization and fostering the development of valid therapeutic options for SCI patients in the future (reviewed in [ 84 , 85 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies will probably help clarifying which is the most optimal source for the development of large-scale therapies in humans. The banking of fully characterized HLA-matched/ablated ESC and iPSC lines produced under cGMP conditions will allow the use of the same lines in both preclinical and clinical studies, favoring standardization and fostering the development of valid therapeutic options for SCI patients in the future (reviewed in [ 84 , 85 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies showed autologous hiPSCs-derived dopaminergic neurons, and retinal cells were safe and effective in treating Parkinson's [80] and macular degeneration [79], respectively, indicating the coming of the hiPSCs-based personalized medicine era. Alternatively, universal hiPSCs can be engineered, for instance, via inactivating major histocompatibility complex (MHC) class I and II genes and overexpressing CD47 or/and PD-L1 [80][81][82][83]. The derivatives of universal hiPSCs are hypoimmunogenic and can be prepared at large scales as "off-the-shelf" allogeneic products.…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of iPSC lines is time-consuming and requires trained operators but once the PSC cells are obtained they are easy to grow, allowing safe production of many cell doses. [ 60 , 61 , 62 , 64 , 65 , 66 , 67 , 68 , 71 , 74 , 95 ] ESC-NSC Only confirmed in animal models. Turmorigenic risk due to potential PSC residues.…”
Section: Clinical Grade Nsc Therapies: Safety Efficacy Scalability and Quality Control Considerationsmentioning
confidence: 94%
“…Although at first iPSC were envisioned to be used in an autologous setting, soon researchers realized that the generation of iPSC under GMP conditions (required for clinical use) for a single patient, is time-consuming, expensive, and hardly viable, and therefore, most clinical trials with iPSC-derived products are being performed in an allogeneic setting [ 63 ]. The immunological reaction triggered by allogeneic iPSC-NSC can be overcome by co-treatment with immunosuppressant drugs, use of HLA-matched iPSC or HLA ablated iPSC by gene-editing technologies such as CRISPR (reviewed in [ 64 , 65 ]). To facilitate the search for compatible donors and foster the development of cell therapies with iPSC-derived products, iPSC banks with common HLA haplotypes are being created at different locations such as Japan [ 66 ], the United Kingdom [ 67 ], or the Republic of Korea [ 68 ].…”
Section: Nsc Derived From Pluripotent Stem Cellsmentioning
confidence: 99%